Rasionalisasi Kelayakan, Opini Serta Aspirasi Masyarakat Terhadap Skenario Pemekaran Kabupaten Lampung Tengah - Maulana Mukhlis (PUBLICA, 2012)
At the time of evaluation and the Institute of Public Administration Ministry of Internal Affairs shows that most regions of the division in Indonesia does not reach the ideal goal, as expected, the Government of Central Lampung regency actually want to do the expansion. Appropriate alternative scenario, the largest district in Lampung province will be divided into three districts, namely Central Lampung (at this time), District Seputih Seputih West and East District. The purpose of this study was to evaluate the rationalization of Central Lampung regency expansion scenarios and how they impact on the future expansion of Central Lampung (as a parent regions). Rationalization made to the fulfillment of eligibility as stipulated in Government Regulation No. 129 of 2000 as well as the opinions and aspirations of the people of Central Lampung to the expansion scenario. The results showed that the formal technical and administrative as stipulated in Government Regulation No. 129 of 2000, Central Lampung regency eligible to be expanded. On the other hand, the majority of people (81.5%) calls for expansion of Central Lampung regency as well as recommendations for immediate expansion scenario is immediately prepared and proposed to the central government. Although the proposal (the public) to bloom area should not always be taken with a policy of expansion, but the results of two feasibility of the above suggests that the rationality behind the proposed expansion of the public in Central Lampung regency has been fulfilled. Therefore, although the proposed expansion could be completed by a non-expansion policy, the public interest on behalf of rationality, choice of area in Central Lampung regency need to be encouraged and facilitated.